If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5 = 11x + -93 Reorder the terms: -5 + 3x = 11x + -93 Reorder the terms: -5 + 3x = -93 + 11x Solving -5 + 3x = -93 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -5 + 3x + -11x = -93 + 11x + -11x Combine like terms: 3x + -11x = -8x -5 + -8x = -93 + 11x + -11x Combine like terms: 11x + -11x = 0 -5 + -8x = -93 + 0 -5 + -8x = -93 Add '5' to each side of the equation. -5 + 5 + -8x = -93 + 5 Combine like terms: -5 + 5 = 0 0 + -8x = -93 + 5 -8x = -93 + 5 Combine like terms: -93 + 5 = -88 -8x = -88 Divide each side by '-8'. x = 11 Simplifying x = 11
| 6x+21=x+61 | | 4x+32=13x-40 | | 4x+10=-74-10x | | -2x-4=6 | | Lnx=4 | | 7x-12=x-36 | | 11x-25=7x+3 | | 3x+20=7x+0 | | 145-5x=6x+24 | | 5(a+20)=20 | | 1+8x=85+x | | 5a+20=-5 | | w^2+2w-24=0 | | 6x-25=35 | | 2(2x+4)=-24 | | 5x+12=2x-3 | | 7n-3=4n+12 | | 5(a+20)=36 | | 6x-5=13x-89 | | -3x+11=20 | | 4x+11=101-5x | | -7x-11=-4x-23 | | 7(2x*x-9x)+5x(9-2x+3x*x)= | | 5a+20=36 | | -2x+22=5(3x+1) | | 2x+40=12x-80 | | 8x+21=-3 | | 5(a+20)=75 | | 4(9-5r)= | | -5x-14=21 | | 5x+45=8x+12 | | 5a+20=120 |